RIZQI DALAM AL-QUR’AN - Simanjuntak, Dahliati (IAIN Padangsidimpuan, 2019)
Rizqi said often heard by us in everyday life. However, not everyone knows and understands the true meaning of Rizqi. Most people who think that Rizqi is only in the form of assets or money. Humans often see the rizqi only a matter of money generated from his labors to work, even though the rizqi of God is very broad. Basically, Rizqi is not only in the form of assets or money. If people knew this, surely they would always be grateful to Allah for what they have. The real meaning of Rizqi is everything that is beneficial that Allah permits for humans, be it clothing, food, wife and children